APPROACH TO CIVIL DISOBEDIENCE: THE COLOMBIAN CASE (2022)
A society that demonstrates against the mandateof a law, government policy or any decision emanating from the public power, starts from a mood that alleges a certain injustice. What is problematic, then, is when the demonstrations are carried out with violence. In this way, the discourse of civil disobedience becomes relevant for its call to peaceful action in a context of social crisis, nonconformity with the actions of public power and decadence of democratic institutions. For this reason, it is of interest to recall civil disobedience and its understanding as an act of resistance, in addition, to elucidate on its understanding in the Colombian case based on the references granted by the constitutional court, jointly, to reflect on the spokesmanship of this act by political leaders and the demonstrations occurred in the 2019-2020 periods. And in this way, to expose the scene on civil disobedience in the Colombian case. Without ignoring that on the subject there is little clarity in its recognition and few pronouncements by the constitutional court, leaving adrift a confused association of the various types of resistance, confused with each other, intended as civil disobedience.